Networks merge - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1992)
Three African feed resources networks are to merge: the African Research Network for Agricultural By-products, the Pasture Network for Eastern and Southern Africa, and the West and Central African Feed Resources Network. The new network will be...